RESEARCH METHOD OF STATIONARY VIBRATIONS FOR NONLINEAR SYSTEMS WITH MONOHARMONIC PERTURBATION - Михайленко, Василь Васильович; Михайленко, Станіслав Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Stationary solutions of equations that describe the behavior of nonlinear system in a monoharmonic load are studied.